Basics of Geomatics - Gomarasca, Mario A. (Springer Netherlands : Imprint: Springer, 2009)
This volume presents a comprehensive and complete treatment. In a systematic way the complex topics and techniques are covered that can be assembled under Geospatial Information namely, Geodesy, Cartography, Photogrammetry, Remote Sensing, Informatics, Acquisition Systems, Global Positioning Systems, Digital Image Processing, Geographic Information Systems, Decision Support Systems, and WebGIS. It describes in detail and at an accessible level - too much math has been avoided - the state of current knowledge. Per chapter a detailed bibliography has been included. As such, it will serve as a working tool not only to geoscientists and geographers but also to engineers, architects, computer scientists, urban planners, specialists in GIS, remote sensing, forestry, agricultural science, soil science geometry, environmental scientists and managers. Applications can be found in security, risk management, monitoring, info-mobility, geo-positioning, food traceability, etc. From the reviews: "The book is rigorous and synthetic, describing with precision the main instruments and methods connected to the multiple techniques today available. The objective pursued is to publish an integrated text, containing simple and comprehensible concepts relevant to experts in Geo-spatial Information." S. Dequal, Professor of Topography and Photogrammetry, DITAG, Polytechnic of Turin, Italy "This book fills a void of telling and showing the reader how remote sensing as a part of geomatics really works. With a clearly presented historical review up to the present time, the author illustrates the basic theories and use of the different remote sensing sensors and how to analyze the data from them for their application. This book would be a complement to the standard remote sensing books and I would highly recommend it for all land oriented professionals and especially graduate students who need a clear explanation of how remote sensing works". Chris J. Johannsen, Professor Emeritus of Agronomy, Department of Agronomy, Purdue University, West Lafayette, Indiana, USA "Basics of Geomatics" is structured in a clear and effective way into thematic chapters that provide a fundamental, yet comprehensive coverage of each of the major disciplines making up the field of Geomatics. Thanks to its clarity and completeness, the text, supplemented by many useful tables and illustrations will serve as a basic reference work for both beginners and experienced readers". John L. van Genderen, Professor, International Institute for Geoinformation Science and Earth Observation (ITC), Department of Earth Observation Science, Enschede, The Netherlands.